THE INFLUENCE OF BUREAUCRATIC BEHAVIOUR ON EMPLOYEE PERFORMANCE IN THE SERVICE OF COOPERATIVES AND SMALL MEDIUM BUSINESS IN BOGOR CITY - Undri, Undri; Zenju, Nandang Saefudin; Heriyati, Ade (Universitas Djuanda, 2021)
Based on the preliminary exploration, the performance of employees in the Small and Medium Enterprises (SME) Cooperative Office of Bogor City is low, as evidenced by several problem indicators. The quality of work of employees in the Non-Formal Small Industry Section, particularly in fostering SMEs (Small and Medium Enterprises), is not adequate, as many of these SMEs have not shown improvement in terms of production or capital. This research aims to analyze the influence of bureaucratic behavior on the performance of employees in the SME Cooperative Office of Bogor City. The research method used in this study is explanatory survey. Based on the results of statistical tests, it was found that bureaucratic behavior, empirically, has a significant impact on the performance of employees in the SME Cooperative Office of Bogor City, accounting for 73.1%. The analysis of bureaucratic behavior through individual characteristics, group characteristics, and bureaucratic characteristics has partially influenced employee performance. Among the dimensions of bureaucratic behavior, the group characteristics, including hierarchy, tasks, authority, responsibility, reward system, and control system, have the most significant influence. On the other hand, the smallest influence comes from the principle of bureaucratic characteristics, such as communication within the group, cooperation within the group, and decision-making within the group.